A Systematic Review of the Clinical Performance of Tooth‐Retained and Implant‐Retained Double Crown Prostheses with a Follow‐Up of ≥3 Years. Issue 1 (4th September 2012) - Verma, Rohini; Joda, Tim; Brägger, Urs; Wittneben, Julia‐Gabriela
Abstract Purpose: The objective of this review was to systematically screen the literature for data related to the survival and complication rates observed with dental or implant double crown abutments and removable prostheses under functional loading for at least 3 years. Materials and Methods: A systematic review of the dental literature from January 1966 to December 2009 was performed in electronic databases (PubMed and Embase) as well as by an extensive hand search to investigate the clinical outcomes of double crown reconstructions. Results: From the total of 2412 titles retrieved from the search, 65 were selected for full‐text review. Subsequently, 17 papers were included for data extraction. An estimation of the cumulative survival and complication rates was not feasible due to the lack of detailed information. Tooth survival rates for telescopic abutment teeth ranged from 82.5% to 96.5% after an observation period of 3.4 to 6 years, and for tooth‐supported double crown retained dentures from 66.7% to 98.6% after an observation period of 6 to 10 years. The survival rates of implants were between 97.9% and 100% and for telescopic‐retained removable dental prostheses with two mandibular implants, 100% after 3.0 and 10.4 years. The major biological complications affecting the tooth abutments were gingival inflammation, periodontal disease, and caries. The most frequent technical complications were loss of cementation and loss of facings. Conclusions: The main findings of this review are: (I) double crown tooth abutments and dentures demonstrated a wide range of survival rates. (II) Implant‐supported mandibular overdentures demonstrated a favorable long‐term prognosis. (III) A greater need for prosthetic maintenance is required for both tooth‐supported and implant‐supported reconstructions. (IV) Future areas of research would involve designing appropriate longitudinal studies for comparisons of survival and complication rates of different reconstruction designs.